A companion to Chinese art - Powers, Martin Joseph 1949-; Tsiang, Katherine R. (Chichester, West Sussex, UK Wiley Blackwell, 2016)
"The volume offers a rich insight into China's social and political institutions, religious practices, and intellectual traditions alongside Chinese art history, theory, and criticism. It brings together an international team of scholars from East and West, whose contributions range from an overview of premodern theory, to those exploring calligraphy, fine painting, sculpture, personal accessories, and more. In addition, the companion reflects on social and cultural issues, such as the challenges of comparative history, the role of the artist in society, the contested role of gender in art production, different theories of nature that have evolved over time, and articulates the direction in which the field of Chinese art history is moving. In promoting a comparative understanding of China's long record of cultural production, this volume provides students and scholars of both Asian and non-Asian art history with an exceptional guide to the history of art in China, from its earliest incarnations to the present day." -- Provided by publisher
Court painting Patricia Ebrey -- The culture of art collecting in Imperial China Scarlett Jang -- Art, print, and cultural discourse in early modern China J.P. Park -- Art and early Chinese archaeological materials Xiaoneng Yang -- Figure painting: fragments of the precious mirror Shane McCausland -- The language of portraiture in China Dora C.Y. Ching -- Visualizing the divine in medieval China Katherine R. Tsiang -- Landscape Peter C. Sturman -- Concepts of architectural space in historical Chinese thought Cary Y. Liu -- Time in early Chinese art Eugene Y. Wang -- The art of "ritual artifacts" (Liqi): discourse and practice Wu Hung -- Classification, canon, and genre Richard Vinograd -- Conceptual and qualitative terms in historical perspective Ronald Egan -- Imitation and originality, theory and practice Ginger Cheng-chi Hsu -- Calligraphy Qianshen Bai -- Emptiness-substance: Xushi Jason C. Kuo -- Artistic status and social agency Martin J. Powers -- Ornament in China Jessica Rawson -- Folding fans and early modern mirros Antonia Finnane -- Garden art Xin Wu -- Commercial advertising art in 1840-1940s "China" Tani E. Barlow -- Words in Chinese painting Alfreda Murck -- On the origins of literati painting in the Song Dynasty Jerome Silbergeld -- Poetry and pictorial expression in Chinese painting Susan Bush -- Popular literature and visual culture in early modern China Jianhua Chen
Includes bibliographical references and index.
Keywords: Art, Chinese